Recycling household waste : the way ahead (Published by Telford for the Institution, 1991)
In 1990 the UK Government's White Paper, 'This Common Inheritance', set a target of recycling half our recyclable household waste, about 25 percent of all household waste, by the end of the century. This book gives a detailed analysis of the potential for improving collection methods and expanding the market for recycled materials. It also gives valuable practical experience from six recycling trials currently in progress in towns throughout the UK, detailing their methods, achievements and costs. It concludes with an analysis of the options for financing the recycling of 25 percent of household waste.